Molecular Marker Assisted Screening of soyabean germplasm for quality characteristics - Pokharel, Shreejan; Bhattarai, Namita; Acharya, Ramesh; Khanal, Bingya Chandra (Journal of Nepal Agricultural Research Council, 2023)
Soybean (Glycine max) is a one of the most valued crop in the world and an emerging crop in Nepal, with increasing cultivation in recent years in Nepal. The crop has gained popularity due to its high protein content and potential as a substitute for traditional protein sources, such as meat and dairy. Soybean is an important source of protein and oil and is widely cultivated for both food and industrial purposes. Marker-assisted screening (MAS) utilizing simple sequence repeat (SSR) markers has been used to pinpoint the genes that regulate the protein and oil content in soybeans. In this work, soybean germplasm were screened for the presence of particular markers associated with the genes regulating protein and oil using Five SSR markers (Satt556, Satt006, Satt212, Satt144 and Satt449) across eighty eight genotypes found in Nepal. The outcomes of this study showed promising results with presence of protein and oil genes on Nepalese genotypes indicating that SSR markers may be successfully utilized to pinpoint soybean genotypes with enhanced protein and oil content having potential increasing the quality and nutrition value.